Influence of Price, Product Quality Towards Consumer Purchase Decisions That Impact on Customer Satisfaction CV. Cahaya Citrasurya Indoprima Surabaya - Rismawati Sitepu; Bangun, Wilson; Aprilia Yustanti , Ovie (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2020)
This study aims to make marketers know that price, product quality on consumer purchasing decisions have an impact on customer satisfaction, namely on Prices, Product Quality on Consumer Purchase Decisions That Impact on Customer Satisfaction CV.Cahaya Citrasurya Indoprima Surabaya. This study using path analysis (path analysis ) and the type of research quantitative population study is a customer CV. Cahaya Citrasurya Indoprima Surabaya, amounting to 50 permanent customers . The sampling technique uses nonprobability techniques(saturated sample) so that the research sample was 50 respondents. Test equipment used for data processing using SPSS software version 24.0. After testing the proposed hypothesis, it is obtained the results of analysis of research data that has been done partially which shows that Product Price and Quality have a significant effect on Purchasing Decisions , indicating that Price and Purchasing Decisions have no significant effect on Customer Satisfaction, indicating that Price, Quality Product and Purchase Decisions have a significant effect on Customer Satisfaction .